Moderating effect of institution on relationship between foreign direct investment, economic growth and pollution - Tun, Yin Li (2019)
Evidence shows that the benefits brought by foreign direct investment (FDI) are not uniformly enjoyed by all FDI recipients. Several recent literatures suggest that this ununiformed is due poor domestic condition such as human capital, financial markets, trade openness, economic freedom, formal institution, etc. The present study takes its cue from recent literature which emphasise on the importance of institutions in economic performance. This is because institutions are critical in determining transaction and production cost, resources allocation, business networking, and overall decision making. Three dimensions of institutions covered in this thesis are competition, business environment and corruption. The first objective examines the role of competition plays in moderating the growtheffect of FDI. To test this objective empirically, this study uses a sample of 117 countries over 2000-2014 period. Using System Generalized-Method-of-Moment (GMM) panel estimator, the findings reveal that the interaction term between competition and FDI (which is used to capture the moderating effect of competition) enters the estimated equation with a positive sign and statistically significant at the 1% level. This finding implies that the effect of FDI on growth is increasing along with the level of competition. The next objective is to investigate the role played by business environment reforms on the impact of FDI on economic growth. Using two-stage least square estimator on this cross section analysis with a sample of 103 countries, over the averaging data from the year 1976 to 2015, exhibits that business environment is critically important in moderating the growth effect of FDI and this result robust to several sensitivity checks. The final objective provides insights into the role played by corruption in the link between FDI and pollution. To test the conditional effect of FDI on pollution through the level of corruption, static threshold regression analysis is adopted and a sample of 70 developing countries over 2003-2013 period is chosen. The result reveals that FDI-pollution link depends on the level of corruption. Specifically, the impact is positive when corruption level is high. This finding is consistent with the view that a more corrupted environment attracts a more polluted industry. This thesis provides empirical evidence on the importance of improving competition and business environment for better FDI spillovers. Accordingly, the government should revoke the entry barriers, reduce intervention in credit market, and abolish minimum wage law to promote competition directly in the market thus allowing the market to function efficiently. Other than that, business environment can be improved by easing business start-up cost, reducing red-tape, improve property registration, easy access to credit and providing tax incentive. Finding from the third objective shows combatting corruption is necessary to reduce the pollution brought by FDI. Combat corruption through offering a higher salary to civil servants is needed to be considered by policy maker. In addition, government should fully utilize the social media platform as another powerful tool to fight corruption.